“GukKatura” Tafsiran Ornamentasi Suling Kesenian Musik Tradisional Sebuku Menggunakan Instrumen Eksperimental Kedalam Komposisi Musik Karawitan: GukKatura”: Interpretation of Flute Ornamentation in the Traditional Music of Sebuku Using Experimental Instruments in a Karawitan Music Composition - ansyah, Sapri; Surya Rahman; Erlinda (LPPM ISBI Bandung, 2024)
This article presents the creation of a new karawitan music composition titled “GukKatura”, inspired by the Singuk ornamentation technique found in the Gayo flute (Suling Gayo) performance of the Sebuku (Pepongoten) tradition from Central Aceh. The main focus is the musical interpretation of the Acciaccatura ornament, perceived as a leaping grace note, and reimagined through a reinterpretative approach. The composition incorporates a range of experimental instruments such as drone flute, PVC saxophone, and fujara, and utilizes compositional techniques including call and response, interlocking, hocketing, and polymeter. The creative process involved field observation, interviews with tradition bearers, instrument exploration, and performance realization. GukKatura introduces a fresh perspective in transforming traditional ornamentation into a contemporary composition, contributing to the enrichment of Indonesian karawitan music.